Challenge Trials: What Are the Ethical Problems?. Issue 1 (25th November 2020) - Hausman, Daniel M
Abstract: If, as is alleged, challenge trials of vaccines against COVID-19 are likely to save thousands of lives and vastly diminish the economic and social harms of the pandemic while subjecting volunteers to risks that are comparable to kidney donation, then it would seem that the only sensible objection to such trials would be to deny that they have low risks or can be expected to have immense benefits. This essay searches for a philosophical rationale for rejecting challenge trials while supposing that they have huge benefits and relatively low risks. Although it finds some force in objections to challenge trials grounded in the obligations of researchers to limit the harms imposed on some individuals for the benefit of others, it argues that there is no compelling objection to challenge trials of vaccines for COVID-19—if they have the benefits and risks that have been claimed.